Determining Intern Nurses Levels in Ethical Sensitivity and Empathy - Cevheroglu, Seda (Galenos Publ House, 2024)
Objective: This descriptive study was designed to determine the ethical sensitivity and empathy levels of intern nurses. Method: The sample of this descriptive and cross-sectional study consisted of 100 fourth-year students enrolled in the nursing department of a foundation university. Data were collected using a descriptive information form, the modified moral sensitivity questionnaire for student nurses (MMSQSN), and the basic empathy scale (BES). Results: It was determined that 68.0% of the intern nurses participating in the research were women, 79.0% chose the profession willingly, 91.0% found the profession suitable, 13.0% experienced ethical problems frequently during their internship, and 62.0% experienced ethical problems from time to time. The MMSQSN and BES scores were 5.29 +/- 0.69, and 71.06 +/- 13.38, respectively. A statistically significant difference was found between age, perception of a good fit, belief in the suitability of the profession, and experience of ethical problems during the internship and MMSQSN. There was also a statistically significant difference in empathy levels, gender, and experience with ethical problems during the internship and BES. Conclusion: Intern nurses had significantly high levels of ethical sensitivity and above-average levels of empathy. Ethical sensitivity levels were higher among students who were 23 years old and older, believed that nursing was a good fit for them, and experienced ethical problems during their internship. On the other hand, empathy levels were higher among female intern nurses who experienced ethical problems during their internship. Therefore, to enhance students' ethical sensitivity and empathy skills, educational methods such as scenario-based learning, psychodrama, and role play are recommended.
Keywords: Ethical sensitivity; empathy; nursing; intern nurse; ethic